POTENSI PELANGGAN PDAM KOTA PEKALONGAN (Survei di Kecamatan Pekalongan Barat) - CATUR RAGIL SUTRISNO (Jurnal Ekonomi Dan Bisnis, 2017)
Thi s study was conducted to determi ne the characteri sti cs of non-househol d customers and potenti al customers PDAM Kota Pekal ongan candi dates, especi al l y i n the Distri ct of Pekal ongan Barat. Thi s research i s a fi el d research by usi ng survey methods. The obj ect of thi s research i s Pekal ongan Barat Distri ct of soci ety thathave not become a customer of PDAM Kota Pekal ongan. The resul ts showed that most househol ds non PDAMservi ces occupy a permanent home and i s i n the settl ement contai ned servi ce network taps, usi ng the water forwashi ng, bathi ng, dri nki ng, ki tchen suppl i es, and water the pl ants from ground water, publ i c hydrants, and buyi ng (non PDAM). The mai n reason of househol ds use water i ns tead of taps i s cheaper and easi er / practi cal than the servi ce water taps. There are 7 non mi ni stry househol d taps i n the Distri ct of Pekal ongan Barat whohave the wi l l i ngness and the abi l i ty to uti l i ze the servi ce of PDAM Kota Pekal ongan, accompani ed by the desi refor cheap and affordabl e i nstal l ati on costs, as wel l as the method of payment by i nstal l ments. Potenti al customers i n the Distri ct of Pekal ongan Barat taps as much as 1,344 househol ds. Proj ected to customers PDAMKota Pekal ongan Servi ces wi l l conti nue to i ncrease al ong wi th the growth i n popul ati on, the economi c capaci tyof househol ds, as wel l as awareness of the i mportance of cl ean and heal thy water.Keyword : non-household customers, potential customers